Digital Marketing Strategies and Their Impact on Business Performance in Small and Medium Enterprises within the Education Sector in Malaysia: A Systematic Literature Review - Zamri, Nur Atiqah Binti; Abdul Rahim, Ramita; Norizan, Norsabrena Binti (Advances in Social Sciences Research Journal, 2024)
Digital marketing is an economical and cutting-edge method to effectively connect with and captivate people on the internet. Nevertheless, the extent to which small as well as medium companies (SMEs) in the education field in Malaysia have embraced and experienced the effects of digital marketing tactics remains uncertain. This systematic review seeks to address the following research inquiries: (1) What are the digital marketing tactics used by small and medium-sized enterprises (SMEs) in the education industry in Malaysia? (2) What is the impact of digital marketing on the commercial performance of small and medium enterprises (SMEs) in the education sector in Malaysia? We have discovered 12 papers that fulfill our criteria for inclusion, consisting of 10 surveys, one quasi-experimental research, and one case study. The outcomes showed that digital marketing had a encouraging and substantial impact on the operational effectiveness of small and medium-sized enterprises (SMEs) operating in the education industry in Malaysia. The average magnitude of this impact was measured at 0.45, with a confidence interval of 95% ranging from 0.32 to 0.58. This systematic review presents data supporting the efficacy and advantages of digital marketing as a strategy for small as well as medium enterprises (SMEs) in the education field in Malaysia. SMEs may enhance their company performance by using digital marketing to augment their online presence, expand their reach, and foster consumer interaction”.